EFEKTIVITAS PENYELENGGARAAN ADMINISTRASI PEMERINTAHAN DESA DI DESA TOBELOS KECAMATAN IBU KABUPATEN HALMAHERA BARAT - Dolosi, Dandres; Dengo, Salmin; Kolondam, Helly febrina (JURNAL ADMINISTRASI PUBLIK, 2018)
The purpose of this research is to know the effectiveness of village administration administration in TobelosVillage, Ibu Hal District West Halmahera District. This research uses quantitative approach method. Theeffectiveness of village administration administration is seen from the three indicators of organizationaleffectiveness proposed by Gibson that is production, efficiency, and adaptation or flexibility. The researcher isthe Village Head, Head of Administration Affairs, Head of Development Affairs, Chairman of BPD, Chairmanof LPM, Chairman of RT 02, and a community figure, totaling 7 people. Data was collected using interviewguidelines, while the analytical technique used was interactive model analysis from Miles and Hubernan.Based on the result of data analysis, it is concluded that the effectiveness of administration administration ofTobelos village seen from the indicator of production, efficiency, and adaptation / flexibility is still not good.Based on the results of research can be recommended suggestions: 1. Quality of human resources of villageheads and village apparatus needs to be improved through training or upgrading. 2. The sources of villagegovernment's financial revenue such as ADD and other sources of revenue mandated in Law No. 6 Year 2004should be optimized. 3. Village Heads and Village Devices should be provided with a fixed income and adequateallowances. 4. Working facilities at village head offices need to be adequately provided for the smoothimplementation of village apparatus tasks.Keywords: Effectiveness, Administration, Village Goverment.